(untitled) (Journal of the Bangladesh Agricultural University, 2014)
Doxycycline sensitivity against in vitro cultured Babesia gibsoni was evaluated by real-time PCR and parasitemia. The culture of B. gibsoni was successfully continued and mean parasitemia was 4.63% when in vitro drug sensitivity test was started. The drug sensitivity test by the real-time PCR calculated the gene copy number from cultured sample. Even if the complete growth inhibition was at certain concentration, the genomic DNA might remain in existence. The results revealed that the doses of doxycycline 8?M, 16 ?M, 32 ?M and 64 ?M of both real-time PCR and parasitemia inhibited the growth of B. gibsoni in a dose-dependent manner at 96 h and 144 h. We determined the IC50 of doxycycline 17.9 ?M at 96 h and 13.8 ?M at 144 h after treatment using real-time PCR. Morphological observation revealed that the number of parasites decreased per erythrocyte and line shaped parasites increased in erythrocytes with the increased concentration of doxycycline. Doxycycline effectively inhibits the growth of B. gibsoni in vitro. Therefore, doxycycline can be used to treat B. gibsoni infection. Further studies are important to know the doxycycline resistance in B. gibsoni. DOI: http://dx.doi.org/10.3329/jbau.v11i1.18219 J. Bangladesh Agril. Univ. 11(1): 97-102, 2013